Do emotional demands and exhaustion affect work engagement? The mediating role of mindfulness - Karahan Kaplan, Merve; Bozkurt, Gözde; Aksu, Bumin Çağatay; Bozkurt, Serdar; Günsel, Ayşe; Gencer Çelik, Gülşah (Frontiers in Psychology, 2024)
The current paper seeks to elucidate the interrelationships among emotional demands (ED), emotional exhaustion (EE), mindfulness, and work engagement (WE), with an explanation of the mediating role of mindfulness within indicated relationships.Background: Nurses working in a stress-related environment face some emotional challenges.New methods such as mindfulness should be learned; therefore, positive outcomes occur along with new developments.Responses were received from nurses through a self-report questionnaire using the convenience sample technique. 429 nurses from health institutions in İstanbul participated in the study. The PLS-SEM technique was used to test the research model.Results: ED and mindfulness, EE and mindfulness, and mindfulness and WE relationships were found. While mindfulness was a mediator between EE and WE, it was not a mediator between ED and WE.It has been revealed that nurses cope with job-related challenges by being present at the moment with high awareness. Furthermore, mindful nurses also foster positive outcomes.Precautions should be taken because of the nursing shortage. It is better to provide mindfulness training to nursing students in schools before their professional lives. Implementing and using technologies might be helpful for nurses.